2019
DOI: 10.21500/20112084.3627
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Targets in People with Emotional Dependency

Abstract: Objective: To examine the relationship between the components of emotional dependency (ED) with anxious, depressive, and impulsive symptomatology. Method: 98 university students (68% women, age M = 20.2 years, ED = 2.19) responded to the ED Questionnaire (EDQ) (Lemos & Londoño, 2006), the Beck Depression Inventory II (Beck, Steer, & Brown, 2011), the Beck Anxiety Inventory (Beck & Steer, 2011), and the short version of the Barratt Impulsiveness Scale BIS-15S (Spinella, 2007). Results: The structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…While analyses show a positive correlation between relational beliefs and emotional dependency, no such relation can be said to exist regarding communication skills. Whereas unsatisfied emotional needs are prioritized in emotional dependency (Lemos et al, 2019), cooperative facilitation of emotional, cognitive, and behavioral skills is observed in communication. It is concluded that the reason for the two variables to have no meaningful relation between them results from this contrast.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While analyses show a positive correlation between relational beliefs and emotional dependency, no such relation can be said to exist regarding communication skills. Whereas unsatisfied emotional needs are prioritized in emotional dependency (Lemos et al, 2019), cooperative facilitation of emotional, cognitive, and behavioral skills is observed in communication. It is concluded that the reason for the two variables to have no meaningful relation between them results from this contrast.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, emotional dependency consists of patterns related to unsatisfied emotional needs in a relationship. Emotional needs that are not satisfied might also lead the individual to pursue intimate relations in desperation (Lemos, Vasquez, & Roman-Calderon, 2019). In cases with emotional vulnerability present, the individual, rather than establishing a bond, becomes dependent and an increase in irrational beliefs is observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Емоційну залежність визначають як стійкі прояви емоційних потреб, які особа намагається задовольнити у близьких міжособистісних стосунках (Castelló, 2005). Дану особливість можна розглядати як особистісну рису, яка має характерні когнітивні, емоційні, мотиваційні та поведінкові складові, що особливо яскраво проявляються у ситуаціях реальної чи ймовірної розлуки з партнером (Lemos, Vásquez & Román-Calderón, 2019). У романтичних стосунках схильні до емоційної залежності особи частіше та інтенсивніше переконані у своїй залежності від партнера, переживають страх самотності та сепараційну тривогу, підлаштовують свою поведінку під очікування партнера та надмірно потребують його чи її уваги (Lemos & Londoño, 2006).…”
Section: емоційна залежність у романтичних стосунках: роль несприятливого дитячого досвіду та ранніх дисфункціних схемunclassified
“…En cuanto a la teoría que guía este tipo de intervenciones, a la que más se recurre es a la teoría cognitiva-conductual, que muestra grandes avances en esta modalidad, además de que trabaja mayormente con población con algún tipo de trastorno adaptativo o emocional, en el cual esta teoría reporta un gran potencial. Por último, hablando de los pacientes que acuden a esta modalidad, se han hecho terapias tanto individuales y grupales con resultados eficaces; estos sujetos son personas con alguna discapacidad para tener acceso presencial por condiciones geográficas, de salud, monetarias o, en su mayoría, por presentar una gravedad severa en sus trastornos, lo que limita el desplazamiento de estos hasta la consulta(Lemos et al, 2019). Acerca de las ventajas y desventajas de este tipo de terapia, se ha encontrado un gran impacto de ellas en el entorno clínico, donde se han sabido posicionar, al demostrar su gran efectividad y calidad en el mejoramiento de los pacientes con algún trastorno psicológico de gran avance, ya sea depresión o ansiedad.…”
unclassified